Prevalência de lesões pré-neoplásicas e neoplásicas malignas de colo uterino nas mulheres atendidas no Hospital Fundação Santa Casa de Misericórdia do Pará - ARAUJO, Adriano Villacorta Lira de (2023)
The invasive cancer of uterine cervix occupies, in a world context, the second position between the MOST frequent malignants neoplasies and it is the most common in developing countries. The objective of this research is to verify the prevalence of the preneoplasics and malignant neoplasics of the uterine cervix in women taken care of in the service of colposcopy of the Hospital Fundação Santa Casa de Misericórdia do Pará. Therefore, became realized an epidemiologist, descriptive, retrospective study, from the analysis of the medical records of the patients taken care of at the Hospital Santa Casa de Misericórdia do Pará, in the period of January 2006 to june 2007, that had been submitted in the biopsy of uterine cervix, being disrespected the analysis of the oncotic colpocitology. After the application of the exclusion criteria, entered, in the study, 222 patients, which had showed average age of 37.5% years old, 22.5% with the secondary incompleted grade, 36.9% were unmarried and just 14.9% of the patients had affirmed that smoke. In ginecoobstetrics antecedents, was verified: major prevalence in the first sexual relationship age between the 15 and 18 years old (43.2%), patients with a lot of childbirths (46.8%) and 62.2% had presented up to 5 partners in their sexual life. In relation to the prevalence of the colposcopic findings, 81.5% were normal; 2.3% were miscellany and only 7.7% were suggestive of invasive cancer. However, 8.6% of the medical records had not presented the description of the colposcopic findings in a valid form for the research. About the frequency of the histopatologics findings, it had a predominance of the findings that determine normality (45.9%), followed for 13.1% of invasive squamous cells carcinoma and for injury of high degree (11.3%). When made the correlation between the colposcopic findings and the histopatologics results, was evidenced one high degree of agreement of the two disgnostic methods, what shows one high positive predictive value for the colposcopia. Although these findings, it became important to express that the accomplishment of the biospy is essential for the confirmation of the diagnosis of cervical injuries. To reduce the high taxes of uterine cervix cancer observed, as well as preneoplasic injuries, it is important that educational campaigns become realized, aiming at to acquire knowledge to the population of the necessity of the preventive examination. The elaboration of a system of convocation of the women, mainly those that are situated in the age band of bigger risk and that they had never made the examination, would be of great value. This system of convocation can be carried through by the agents of health of the Family Health’s Program, that comes presenting great success in terms of prevention in all the areas of the medicine.